Epigenetic-based therapies for Friedreich ataxia - Sandi, Chiranjeevi; Sandi, Madhavi; Anjomani Virmouni, Sara; Al-Mahdawi, Sahar; Pook, Mark A. (Frontiers in Genetics, 2014)
Friedreich ataxia (FRDA) is a lethal autosomal recessive neurodegenerative disorder caused primarily by a homozygous GAA repeat expansion mutation within the first intron of the FXN gene, leading to inhibition of FXN transcription and thus reduced frataxin protein expression. Recent studies have shown that epigenetic marks, comprising chemical modifications of DNA and histones, are associated with FXN gene silencing. Such epigenetic marks can be reversed, making them suitable targets for epigenetic-based therapy. Furthermore, since FRDA is caused by insufficient, but functional, frataxin protein, epigenetic-based transcriptional re-activation of the FXN gene is an attractive therapeutic option. In this review we summarise our current understanding of the epigenetic basis of FXN gene silencing and we discuss current epigenetic-based FRDA therapeutic strategies.